Raveneliopsis, a new genus of ravenelioid rust fungi on Cenostigma (Caesalpinioideae) from the Brazilian Cerrado and Caatinga. (4th March 2023) - Ebinghaus, Malte; dos Santos, Maria D. M.; Tonelli, Guilherme S. S. S.; Macagnan, Dirceu; Carvalho, Eudes Arruda; Dianese, Jose C.
ABSTRACT: The multicellular discoid convex teliospore heads represent a prominent generic feature of the genus Ravenelia . However, recent molecular phylogenetic work has shown that this is a convergent trait, and that this genus does not represent a natural group. In 2000, a rust fungus infecting the Caesalpinioid species Ce nostigma macrophyllum (= C. gardnerianum ) was described as Ravenelia cenostigmatis . This species shows some rare features, such as an extra layer of sterile cells between the cysts and the fertile teliospores, spirally ornamented urediniospores, as well as strongly incurved paraphyses giving the telia and uredinia a basket-like appearance. Using freshly collected specimens of Rav. cenostigmatis and Rav. spiralis on C. macrophyllum, our phylogenetic analyses based on the nuc 28S, nuc 18S, and mt CO3 (cytochrome c oxidase subunit 3) gene sequences demonstrated that these two rust fungi belong in a lineage within the Raveneliineae that is distinct from Ravenelia s. str. Besides proposing their recombination into the new genus Raveneliopsis (type species R. cenostigmatis ) and briefly discussing their potentially close phylogenetic affiliations, we suggest that five other Ravenelia species that are morphologically and ecologically close to the type species of Raveneliopsis, i.e., Rav. corbula, Rav. corbuloides, Rav. parahybana, Rav. pileolarioides, and Rav. Striatiformis, may be recombined pending new collections and confirmation through molecular phylogenetic analyses.